Dilution in New Zealand: The Effects of the Tarnishment Limb of Dilution on Free Speech - Sims, Alexandra (Victoria University of Wellington Law Review, 2001)
Calls have been made to introduce trade mark dilution into New Zealand ’s trade mark legislation. Currently trade mark protection is limited to the same or similar goods or services to those over which the trade mark is registered, and within this class only certain uses of that trade mark are protected. The positive associations the selling power of famous trade marks is such that their use on dissimilar goods or services can make those goods or services more attractive to consumers. Trade mark dilution recognises that such unauthorised use will weaken the famous trade mark’s selling power and proscribes such use. Trade mark dilution, however, goes further and removes the distinction currently made between different uses of a trade mark. Infringement occurs if unauthorised use of the trade mark damages the positive associations the trade mark invokes. Unless exceptions are made to the latter aspect of trade mark dilution, the impact of trade mark dilution upon free speech will be significant.